Mohon dibantu kak.soalnya mau dikumpulin besok!!! Pleaseee
Invers dan komposisi fungsi
fungsi komposisi
dan Invers
*
f(x) = (2x – 1)/ (x + 1)
g(x) = 3x – 1
*
f(x)= (ax + b)/ (cx +d) –> f⁻¹(x) = (dx – b)/(-cx +a)
*
gof(x)= g { f(x) } = g { (2x -1) / (x + 1)}
gof(x) = 3(2x -1 ) / (x + 1) - 1
gof(x) = (6x -3)/(x + 1) – (x – 1)/(x -1)
gof(x) = (6x -3 -x + 1) / (x- 1)
gof(x)= (5x – 2)/ (x-1)
*
fog (x)= f { g(x)} = f (3x – 1)
fog(x) = { 2(3x – 1) – 1 } / { 3x -1 + 1}
fog(x) = ( 6x – 2 – 1) / (3x)
fog(x) = (6x – 3) / (3x) = 3(x – 1)/ 3(x)
fog(x) = (x – 1)/x
*
c) {f⁻¹ o g⁻¹) x = (gof)⁻¹(x)
(gof)(x) = (5x – 2)/ (x-1)
(gof)⁻¹(x) = (x + 2)/(-x + 5)
{f⁻¹ o g⁻¹}(x) = (x + 2) /(-x +5)
*
e) {g⁻¹ o f⁻¹)(x) = (fog)⁻¹ (x)
fog(x) = (x -1)/(x)
(fog)⁻¹(x)= (x + 1) /(-x)
{g⁻¹ o f⁻¹}(x) = (fog)⁻¹(x)= (x + 1)/ (-x) = – (x +1) /(x)
*
f) {gof}⁻¹ (x) =
(gof)(x) = (5x – 2)/ (x-1)
(gof)⁻¹(x) = (x + 2)/(-x + 5)